Metallogel Template Fabrication of pH‐Responsive Copolymer Nanowires Loaded with Silver Nanoparticles and Their Photocatalytic Degradation of Methylene Blue. Issue 10 (11th August 2014) - Wen, Xing; Tang, Liming; Li, Botian
Abstract Poly(N, N′‐methylenebisacrylamide–4‐vinylpyridine) (P(MBA‐4VP)) nanowires loaded with silver nanoparticles (Ag NPs) have been fabricated by silver metallogel template copolymerization, and subsequently, silver ions are reduced instead of the template being removed. Ag NPs with a diameter of 5–15 nm were dispersed throughout the core of P(MBA‐4VP) nanowires. The size and distribution of the formed Ag NPs could be finely controlled by reduction time. The pH sensitivity of P(MBA‐4VP) nanowires offers the possibility of Ag NP release from the nanowires under acidic conditions. The photocatalytic performance of the P(MBA‐4VP) nanowires loaded with Ag NPs was evaluated for the degradation of methylene blue (MB) under UV light irradiation. Their rate of degradation is dependent on the content and size of the Ag NPs, as well as the pH values of the MB solution. Moreover, the P(MBA‐4VP) nanowires loaded with Ag NPs exhibited high photostability, and the photocatalytic efficiency reduced by only 1.81 % after being used three times.